Sistem Monitoring Kontrol Kecepatan Motor 3 Phase Berbasis Internet Of Thing (IoT) - Volta, Yonki Alexander; Nofiansah; Herman Yani; Fadil Asnani; Carolina, Yuni; Hidayat, Risqy (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Three-phase induction motors are widely used in industry due to their reliability and efficiency. However, manual speed control systems limit flexibility and operational efficiency. This study aims to design a three-phase motor speed monitoring and control system based on the Internet of Things (IoT) by integrating an ESP32 microcontroller and a Variable Speed Drive (VSD). The system is controlled in real time using two applications: Blynk for control and Smart Life for power monitoring. Testing was carried out by varying the frequency from 10 Hz to 50 Hz, observing voltage, current, and motor rotational speed (RPM). The results show that an increase in frequency is directly proportional to the increase in motor speed, with a detected current imbalance between phases, indicating the need for additional protection. The system demonstrates precise, responsive control and is feasible for automation in small to medium-scale industries.